HUBUNGAN PENGETAHUAN KESEHATAN GIGI DAN MULUT DENGAN KEBERSIHAN GIGI DAN MULUT PADA ANAK DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KELAS I MARTAPURA - Dwi Fitriarum Sari Fitriarum Sari; Metty Amperawati; Naning KU Naning (Poltekkes Kemenkes Banjarmasin, 2020)
Dental caries is caused by the low degree of dental and oral hygiene and is the biggest disease among the population of Indonesia. Dental and oral health efforts need to be viewed from an environmental aspect as well as awareness of the degree of dental and oral hygiene. From the results of a preliminary study conducted by researchers on 10 children, it is known that 20% of children with an OHI-S average of 4.2 (poor), 60% of children with an average OHI-S of 1.87 (moderate) and 20% of children with an OHI-S average of 0.88 (good). The purpose of this study was to determine the relationship between knowledge of oral health and dental and oral hygiene in children in the Class I Martapura Special Development Institute. Analytical survey research method with cross sectional approach design. Sampling was total sampling with a sample size of 37 children. Data collection using a questionnaire to see children's knowledge. Oral hygiene is seen by using the OHI-S index. Data presented in the form of frequency distribution and percentage then analyzed using the chi square test. The results showed most of the knowledge of dental and oral health was in good category (51.4%) and dental and oral hygiene was in good category (51.4%). From the statistical results, it was found that there was no significant relationship between knowledge of dental and oral health with dental and oral hygiene (p> 0.05). The conclusion of the study was that there was no relationship between knowledge of oral health and dental and oral hygiene in children at the Martapura Class I Special Development Institute. It is recommended that correctional students pay more attention to dental and oral hygiene by brushing their teeth every morning after breakfast and at night before going to bed. Key words: Knowledge of dental health, oral hygiene